2014
DOI: 10.1007/s13197-014-1656-4
|View full text |Cite
|
Sign up to set email alerts
|

Transgalactosylating β-galactosidase from probiotic Lactobacillus plantarum MCC2156: production and permeabilization for use as whole cell biocatalyst

Abstract: Key nutritional factors were optimized for the maximum production of transgalactosylating β-galactosidase from Lactobacillus plantarum MCC2156. Galactose, yeast extract, sodium acetate and manganese sulphate were the most important nutrients affecting β-galactosidase production. Maximum β-galactosidase production (3015 miller units) was obtained by culturing L. plantarum in the optimized fermentation medium containing (w/v) galactose (4 %), yeast extract (2 %), sodium acetate (3 %) and manganese sulphate (0.07… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Glucose is the most prevalent monosaccharide used by lactic acid bacteria. In contrast, other studies confirm that L. plantarum , including the SKKL1 strain, effectively consumed lactose in modified MRS medium due to a gene encoding β-galactosidase 20 , 21 to produce a high amount of lactic acid 12 . There should be another limiting factor in milk fermentation that restricts sugar uptake by this bacterium.…”
Section: Resultsmentioning
confidence: 90%
“…Glucose is the most prevalent monosaccharide used by lactic acid bacteria. In contrast, other studies confirm that L. plantarum , including the SKKL1 strain, effectively consumed lactose in modified MRS medium due to a gene encoding β-galactosidase 20 , 21 to produce a high amount of lactic acid 12 . There should be another limiting factor in milk fermentation that restricts sugar uptake by this bacterium.…”
Section: Resultsmentioning
confidence: 90%
“…This result correlates with that from earlier studies that demonstrated the higher permeabilizing efficiency of mixed organic solvents in Lactobacillus spp. and yeast cells compared to individual solvents (Kumari et al, 2011;Gobinath and Prapulla, 2015). Similarly, Meira et al (2012) reported a β-gal activity of 47.7 MU for Lactobacillus casei and a maximum value of 2503 MU for Lactobacillus plantarum when cells were extracted using a mixture of toluene:acetone.…”
Section: Resultsmentioning
confidence: 91%
“…This result correlates with that from earlier studies that demonstrated the higher permeabilizing efficiency of mixed organic solvents in Lactobacillus spp. and yeast cells compared to individual solvents (Kumari et al ., 2011; Gobinath and Prapulla, 2015). Similarly, Meira et al .…”
Section: Resultsmentioning
confidence: 99%
“…L. plantarum Ln1 showed a higher b-galactosidase production (3067.42 mU/ mL) than L. plantarum KCTC 3108 (2128.83 mU/mL) (Table 2). Previously, L. plantarum MCC2156 showed a maximum b-galactosidase production of 3105 mU/mL under optimized conditions (Gobinath and Prapulla 2015). In addition, L. plantarum Ln4 isolated from kimchi produced b-galactosidase at 3320.99 mU/mL (Son et al 2017).…”
Section: Production Of B-galactosidasementioning
confidence: 98%